(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This article discusses the significance of input in the first language acquisition process. Input refers to the linguistic exposure children receive, which plays a fundamental role in their language development. The paper analyzes various theories surrounding input's role, types of input, and its effects on children's linguistic outcomes. Additionally, it explores the implications for language learning, emphasizing the need for high-quality input in diverse learning environments. The findings highlight that optimal input fosters effective language acquisition among children.